Konstruksi Realitas Kolektor Vinyl Musik - Rahmat Alifin Valentino; Agus Rusmana; Ninis Agustini Damayani (Institut Seni Indonesia Denpasar, 2021)
Purpose: This study aims to determine the meanings, motives and experiences of the collectors in collecting Vinyl. Research methods: This study uses a qualitative method with a phenomenological approach. Data collection technique was done by interviewing. Informants in this study are three Vinyl collectors who have been collecting Vinyl for over 5 years and owning hundreds of Vinyl pieces. Results and discussion: The results in this study are (1) the meaning of collecting Vinyl is a representation of the collector’s love for music, Vinyl is a part of life, collecting Vinyl creates an addiction, Vinyl is a basic need, Vinyl is a daily routine, and Vinyl is a transaction tool. (2) The collector’s motive in collecting Vinyl is to appreciate musical works, want to contribute to the preservation of musical works, Vinyl a source of economy, physical factors and sound quality produced by higher quality Vinyl, Vinyl artwork that has aesthetic valued, history value, and the rarity of Vinyl. (3) Collectors’ experience in collecting Vinyl, namely consistency from the past until now collecting Vinyl, continuing to add to the Vinyl collection which numbered in the hundreds to thousands, making sacrifices in terms of finance, other basic needs, and social life in order to buy Vinyl, doing special and intensive care so that the sound and physical quality of Vinyl is maintained, providing a special room for Vinyl collections, and buying and selling and bartering transactions between Vinyl collectors. Implication: The development of technology made the world community switch to listening to music from Vinyl to digital platforms. However, there are still some people who are still loyal to use Vinyl as a medium for listening to music and collecting it.